2014
DOI: 10.3389/fnhum.2014.00729
|View full text |Cite
|
Sign up to set email alerts
|

Processing of acoustic and phonological information of lexical tones in Mandarin Chinese revealed by mismatch negativity

Abstract: The accurate perception of lexical tones in tonal languages involves the processing of both acoustic information and phonological information carried by the tonal signal. In this study we evaluated the relative role of the two types of information in native Chinese speaker’s processing of tones at a preattentive stage with event-related potentials (ERPs), particularly the mismatch negativity (MNN). Specifically, we distinguished the acoustic from the phonological information by manipulating phonological catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 37 publications
8
49
1
1
Order By: Relevance
“…This paradigm could also allow the direct comparison and dissociation of acoustic and phonological information from tonal stimuli by using the same syllable (e.g., /pa/ with different tonal variations in Xi et al, ). It has also been proved effective in previous studies (e.g., Xi et al, ; L. Zhang et al, ; K. Yu et al, ).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…This paradigm could also allow the direct comparison and dissociation of acoustic and phonological information from tonal stimuli by using the same syllable (e.g., /pa/ with different tonal variations in Xi et al, ). It has also been proved effective in previous studies (e.g., Xi et al, ; L. Zhang et al, ; K. Yu et al, ).…”
Section: Introductionmentioning
confidence: 84%
“…These were similar to the findings in Xi et al (), which used the same tonal continuum to explore native speakers’ categorical perception of Mandarin lexical tones. Many other studies have also used this tonal continuum to detect native speakers’ categorical perception of Mandarin lexical tones successfully (Wang et al, ; Xi et al, ; K. Yu et al, ; L. Zhang et al, , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the amplitude of MMN is larger for between- than within-category F0 differences in native Mandarin listeners (Xi et al, 2010; Yu et al, 2014). Ren and colleagues found that MMN was larger when pitch was used phonetically than when it served a prosodic (intonation) function (Ren et al, 2009).…”
Section: Introductionmentioning
confidence: 99%